Experimental study on the thermal performance of loop heat pipe for the aircraft anti-icing system. (August 2017) - Zhao, Y.; Chang, S.; Yang, B.; Zhang, W.; Leng, M.
Highlights: A Double Compensation Chamber Loop Heat Pipe (DCCLHP) for the aircraft anti-icing system was developed. Start-up performance, temperature oscillation and the operation characteristics were analyzed. Different vapor/liquid distribution in the CCs with different heating power and the AOAs were observed. The anti-icing performance was predicted. Abstract: The objective of this research is to experimentally investigate the start-up and operating characteristics of the Double Compensation Chamber Loop Heat Pipe (DCCLHP) anti-icing system. The loop was made of stainless steel with nickel wick, and the working fluid was ethanol. Experiments were carried out with the heat loads from 10 W to 180 W. The angle of attack (AOA) is from −10° to 5°. It was found that: (1) in order to obtain a good anti-icing result, the DCCLHP anti-icing system should be turned on approximately ten minutes before the aircraft encountered cloud with super-cooled droplets; (2) temperature oscillations happened in the start-up process when the AOA is not 0°; (3) the positive AOA can increase the surface temperature, as a result of which the anti-icing effect could also be enhanced.